A Carbon-Stabilized Austenitic Steel with Lower Hydrogen Embrittlement Susceptibility - Khanchandani, Heena; Zeiler, Stefan; Strobel, Lucas; Göken, Mathias; Felfer, Peter (Steel Research International, 2023)
High-strength steels are susceptible to H-induced failure, which is typically caused by the presence of diffusible H in the microstructure. The diffusivity of H in austenitic steels with face-centered cubic (fcc) crystal structure is slow. The austenitic steels are hence preferred for applications in the hydrogen-containing atmospheres. However, the fcc structure of austenitic steels is often stabilized by the addition of Ni, Mn, or N, which are relatively expensive alloying elements to use. Austenite can kinetically also be stabilized using C. Herein, an approach is applied to a commercial cold work tool steel, where C is used to fully stabilize the fcc phase. This results in a microstructure consisting of only austenite and M7C3 carbide. An exposure to H by cathodic hydrogen charging exhibits no significant influence on the strength and ductility of the C-stabilized austenitic steel. While this material is only a prototype based on an existing alloy of different purposes, it shows the potential for low-cost H-resistant steels based on C-stabilized austenite.
CRIS-Team Scopus Importer:2023-11-03
Keywords: atom probe tomography; austenite stabilizations; diffusible hydrogen; electron backscatter diffractions; hydrogen embrittlements